Nursing leadership style and mental health outcome of nurse in Taiwan - Lin, Ping-Yi (2013)
The present thesis report research on the role of leadership style related to the quality of nurses' working lives in Taiwanese hospitals. It begins by focusing on the mental health of nursing work forces and questions the applicability of leadership styles employed in different ownership of health care organisations. There is very little literature on this issue and knowledge of how such hospitals function is not clear. The thesis addresses the influences of nursing leadership style at both the individual and organisational levels examining the perception of nurses and developing a research model using Structural Equation Model (SEM). Both the leader's perspective and subordinate's viewpoint were measured. Two studies were conducted which illustrated the perception of leadership style in Taiwanese healthcare settings. The first study was designed as the qualitative study which used in depth interviews with 21 representatives to explore the current organisation status of hospitals and attitudes towards and interpretation of leadership.